ChemInform Abstract: Tandem Synthesis of Pyrroloisoquinolines Through 5‐endo Iodolactamization, Oxidative Functionalization and α‐Amidoalkylation Reaction. Issue 40 (October 2015) - Tang, Yu; Han, Ranran; Lv, Mingcan; Chen, Yang; Yang, Pan
Abstract The reaction can be performed in two separate steps or in one pot.